The HGF/Met Receptor Mediates Cytotoxic Effect of Bacterial Cyclodipeptides in Human Cervical Cancer Cells - Hernández-Padilla, Laura; Durán-Maldonado, Mayra X.; Martínez-Alcantar, Lorena; Rodríguez-Zavala, José S.; Campos-García, Jesús (Current Cancer Drug Targets, 2025)
BackgroundHuman cervix adenocarcinoma (CC) caused by papillomavirus is the third most common cancer among female malignant tumors. Bioactive compounds such as cyclodipeptides (CDPs) possess cytotoxic effects in human cervical cancer HeLa cells mainly by blocking the PI3K/Akt/mTOR pathway and subsequently inducing gene expression by countless transcription regulators. However, the upstream elements of signaling pathways have not been well studied.MethodsTo elucidate the cytotoxic and antiproliferative responses of the HeLa cell line to CDPs by a transcriptomic analysis previously carried out, we identified by immunochemical analyses, differential expression of genes related to the hepatocyte growth factor/mesenchymal-epithelial transition factor (HGF/MET) receptors. Furthermore, molecular docking was carried out to evaluate the interactions of CDPs with the EGF and MET substrate binding sites.ResultsImmunochemical and molecular docking analyses suggest that the HGF/MET receptor participation in CDPs cytotoxic effect was independent of the protein expression levels. However, protein modulation of downstream Met-targets occurred due to the inhibition of phosphorylation of the HGF/MET receptor. Results suggest that the antiproliferative and cytotoxicity of CDPs in HeLa cells involve the HGF/MET receptor upstream of PI3K/Akt/mTOR pathway; assays with the human breast cancer MCF-7 and MDA-MB-231cell lines supported the finding.ConclusionData provide new insights into the molecular mechanisms involved in CDPs cytotoxicity and antiproliferative effects, suggesting that the signal transduction mechanism may be related to the inhibition of the phosphorylation of the EGF/MET receptor at the level of substrate binding site by an inhibition mechanism similar to that of Gefitinib and Foretinib anti-neoplastic drugs.
Keywords: anti-neoplastic drugs